Effect of salbutamol on the cardiovascular response in healthy subjects at rest, during physical exercise, and in recovery phase: a randomized, double-blind, crossover study - Maiane da Silva Feitoza; Jaqueline Ribas de Melo; Wladimir Musetti Medeiros; Gabriel Grizzo Cucato; Rafael Stelmach; Alberto Cukier; Celso Ricardo Fernandes de Carvalho; Felipe Augusto Rodrigues Mendes (Universidade Estadual Paulista (UNESP), 2017)
ABSTRACT Aim To evaluate the effect of the short-acting beta agonists (SABAs) salbutamol on cardiovascular response rest, exercise and recovery phase. Methods This study was conducted as a randomized, double-blind, placebo controlled, crossover study in 15 healthy adults, with a mean age of 30.2±6.6 years. Participants underwent a maximal effort test on two non-consecutive days with 400 mcg of salbutamol or placebo. Throughout the protocol, the variables HR, blood pressure (BP), perceived rate of effort (modified Borg scale) and peak expiratory flow (PEF) were monitored. Results After salbutamol, baseline HR and PEF had increase from 71±8 to 80±11 bpm (p<0.05) and 454.0±64.5 to 475.3±71.4 L/min (p < 0.05), respectively. The variables HR, BP and Borg were similar between interventions during all the protocol phases (p>0.05). Conclusion Administration of salbutamol increased rest heart rate; however, did not change heart rate, blood pressure and perceived exertion during exercise or recovery. This suggests that the salbutamol administration is safe and does not affect exercise intensity prescription in healthy subjects.